Climate Finance: Global and National Perspectives in the Context of COVID-19 Pandemic Impact - Naumoski, Aleksandar; Angelova, Biljana (Institute of Economics – Skopje, Ss. Cyril and Methodius University in Skopje, 2022)
In this paper we investigated global and national public climate finance. We provide a novel methodology for estimating public climate finance in the government budgets with its application to the case of the City of Skopje. Climate finance globally reached USD 632 bn in 2020 with an annual increase of only 10%, compared to previous years, which grew by about 25%. The achieved level is far from the required USD 4.35 trillion per year to meet climate objectives by 2030. We found that global pandemic of COVID-19 negatively affected the growth of the global climate finance in 2020 and lowered the level of public climate finance in many developing countries. North Macedonia is a small developing country with clear commitment to combating climate change. The Enhanced Nationally Determined Contributions (ENDC) include 63 mitigation policies and measures to reduce GHGs emissions by 51% by 2030, which require EUR 25.03 billion climate investments. Using the methodology for Climate Budget Tagging (CBT), we estimated that the amount of public climate finances of the City of Skopje in 2020 reached USD 6.09 million, which represents as much as 9.07% of the overall budget expenditures for the year, and an increase of 75% from the previous year.
Keywords: climate finance; climate budget tagging (CBT); UNFCC; Enhanced Nationally Determined Contributions (ENDC); North Macedonia